ATP as a Marker for Surface Contamination of Biological Origin in Schools and as a Potential Approach to the Measurement of Cleaning Effectiveness - Shaughnessy, Richard J. (J Occup Environ Hyg, 2013)
To address the need for a quantitative approach to the measurement of cleaning effectiveness, related to biologically derived surface contamination, three commercially available adenosine triphosphate (ATP) test systems were used to collect multiple samples measured in relative light units (RLUs) from 27 elementary schools in the southwestern United States before and after a standardized cleaning protocol. The database consisted of 6480 ATP measurements from four critical surfaces (student desktops, cafeteria tabletops, and restroom sinks and stall doors). Data was assessed according to ranges of ATP values before and after cleaning. Results showed the potential for such data to provide the basis for a standardized approach to the measurement of cleaning effectiveness, based on detection and quantification of pollutant loads of biological origin, across critical surfaces in school building environments. It is anticipated that verification of this data in school buildings across different geographic and climatic regions will lead to the establishment of “acceptable” ranges of ATP values that can be used as a practice-based approach to improving cleaning practices and contributing to healthier school environments.